Creation of a Sudden Cardiac Arrest Safety Net - Mary McCormack; Carole Zarcone; Kendra Hoepper; Pamela Watters (The Ohio State University Libraries, 2021)
Background: More than 350,000 episodes of out-of-hospital cardiac arrest (OHCA) occur annually in the United States, with less than half of the victims receiving bystander cardiopulmonary resuscitation (CPR). Provision of bystander CPR has been noted to increase survival rates two to three-fold; however, bystander CPR is initiated in less than 50 % of out of OHCA episodes in the United States. Aim: The purpose of this pilot study was to create a sudden cardiac arrest safety net on a college campus. The American Heart Association (AHA) CPR in Schools Program© was provided to college students, athletes, faculty and staff. Method: A multi-group educational intervention with a pre- and post-test design. Results: Participant knowledge level of CPR and AED use significantly improved on the post test. Additionally, after attending the sessions participants reported an increase in comfort level performing CPR and improved knowledge of the locations of the AEDs on campus. As a result of the program, nine additional AED's have been placed in high-traffic areas on campus. Conclusion: Empowering laypersons with the skills and knowledge to respond to potential episodes of OHCA are integral steps towards improving patient outcomes.